Vaccination of Pregnant Dams with Intimin(O157) Protects Suckling Piglets from Escherichia coli O157:H7 Infection - Dean-Nystrom, Evelyn A. (American Society for Microbiology, 2002)

(untitled)
Cattle are important reservoirs of enterohemorrhagic Escherichia coli (EHEC) O157:H7 that cause disease in humans. Both dairy and beef cattle are asymptomatically and sporadically infected with EHEC. Our long-term goal is to develop an effective vaccine to prevent cattle from becoming infected and transmitting EHEC O157:H7 to humans. We used passive immunization of neonatal piglets (as a surrogate model) to determine if antibodies against EHEC O157 adhesin (intimin(O157)) inhibit EHEC colonization. Pregnant swine (dams) with serum anti-intimin titers of ≤100 were vaccinated twice with purified intimin(O157) or sham-vaccinated with sterile buffer. Intimin(O157)-specific antibody titers in colostrum and serum of dams were increased after parenteral vaccination with intimin(O157). Neonatal piglets were allowed to suckle vaccinated or sham-vaccinated dams for up to 8 h before they were inoculated with 10(6) CFU of a Shiga toxin-negative (for humane reasons) strain of EHEC O157:H7. Piglets were necropsied at 2 to 10 days after inoculation, and intestinal samples were collected for determination of bacteriological counts and histopathological analysis. Piglets that ingested colostrum containing intimin(O157)-specific antibodies from vaccinated dams, but not those nursing sham-vaccinated dams, were protected from EHEC O157:H7 colonization and intestinal damage. These results establish intimin(O157) as a viable candidate for an EHEC O157:H7 antitransmission vaccine.